Obtención de tres consorcios microbianos de suelos de un bosque primario y comparación de sus capacidades de biodegradación de hidrocarburos aromáticos policíclicos, Región Loreto - Vela del Águila, Pedro Cesar (2024)
Polycyclic aromatic hydrocarbons (PAHs) are a cause of great public concern due to their harmful effects on the environment and human health, which is why there is interest in obtaining consortia composed of different species of PAH-degrading microorganisms. The general objective of this research was to obtain three microbial consortia from soils of a primary forest and compare their capacities for biodegrading polycyclic aromatic hydrocarbons. To do this, the samples were first cultured for 10 days in Bushnell Haas (BH) medium with 1% petroleum. Then, they were cultured for 30 days in BH medium with PAHs, performing subcultures every 10 days. Microbial growth was evaluated by measuring the optical density at 600 nm, and the presence of microorganisms was verified by Gram staining, ethidium bromide staining, and lactophenol blue staining. In addition, metagenomic DNA (mDNA) was purified, followed by spectrophotometric and electrophoretic analysis. Subsequently, mDNA was amplified by PCR. Finally, the biodegrading capacity of the consortia was determined by measuring the total polyphenol (TP) content. Three PAH biodegrading microbial consortia were obtained, consisting of Gram-positive and -negative cocci, bacilli, coccobacilli, and yeasts. Good quality, quantity, and integrity mDNA was also obtained, and successful PCR amplification was achieved. Finally, the biodegradation capacities of the three microbial consortia were compared. In conclusion, three microbial consortia were obtained, and their growth and biodegradation capacities using PAHs were evaluated.